Immune characteristics of severe and critical COVID-19 patients (2020)
Recently, the novel coronavirus disease (COVID-19) has broken out worldwide,1 with rapid increase of infected patients. COVID-19 dominantly leads to pneumonia.2 Among these COVID-19 patients, some appears to be severe symptoms with acute respiratory distress syndrome, organ failure,2 and further present a poor outcome. Previous studies have been reported that immune patterns are closely associated with disease progression of patients infected with other viruses.3 The correlation between immune signatures and outcome of severe and critical COVID-19 cases was not well illuminated. Therefore, we aimed to evaluate the correlation between immune characteristics, especially levels of lymphocytes and cytokines in peripheral blood, and clinical parameters in severe and critical COVID-19 patients, in order to find critical indicators of disease progression and to provide important guides for therapeutic strategy. Thirty-six adult cases with severe and critical COVID-19 were enrolled. The disease outcome, immune patterns, microbiota infection, coagulation profile, and organ dysfunction biomarkers were analyzed and collected. This project was approved by the Ethics Committee of our hospital (No. 2020-KY-060), and all patients signed the informed consent